Community Forestry Research : an Asia-Pacific Overview - Rao, Y. S. (Indian Forester, 1991)
With ever increasing attention being focussed worldwide on forestry in general and community forestry in particular, there is a need to have a closer look at forestry research organisations and their focus of activities. The World Bank, FAO, IUFRO, ACIAR, CIDA, DANIDA, among others, have initiated several programmes to encourage forest research in the Asia-Pacific region, but the shortage of qualified manpower and lack of coordination between beneficiary institutions are major constraints in achieving the goals of these internationally assisted programmes. The assistance needs to be taken fall advantage of, in order to give a fI11ip to the massive afforestation efforts in the region, through a well developed research base.